What the corpse revealed : murder and the science of forensic detection - Miller, Hugh, 1937- (St. Martin's Press, 1999)
Presented here in dramatic detail are sixteen real-life criminal cases taken from the files of forensic scientists all over the world. In What the Corpse Revealed, author and forensic expert Hugh Miller collects these true-crime stories that confounded traditional police detection. Including only those cases solved on the basis of scientific investigation, Miller takes us through each one from the viewpoint of the key actors, and in detailed procedural stages shows how the perpetrators of the crime were found.